Geología de los cuadrángulos de Bayóvar, Sechura, La Redonda, Punta La Negra, Lobos de Tierra, Las Salinas y Mórrope. Hojas: 12a -12b - 12c - 13a - 13b - 13c - 14c - [Boletín A 32] - Caldas Vidal, Julio (1980)
78 p.